Kajian Filosofis Upacara Munggah Deha Di Desa Pakraman Suwat, Kabupaten Gianyar - Ida Ayu Nyoman Sawitri; Ida Bagus Putu Eka Suadnyana (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2021)
The Munggah Deha ceremony is one form of the implementation of the yadnya which is traditionally carried out by Hindus in Pakraman Suwat Village. The Munggah Deha ceremony is held when a child starts to become a teenager which is marked by a change in the voice in boys and in girls is marked by the first menstruation. This traditional ceremony is still being carried out by the community in Pakraman Suwat Village. To get a clearer understanding, a more in-depth study was conducted, so that later the community could find out the form and philosophical meaning contained in the Munggah Deha ceremony which was held in Pakraman Suwat Village, Gianyar Regency. As for the problems that can be formulated, namely: what is the form of the implementation of the Munggah Deha Ceremony, and what is the meaning contained in the Munggah Deha Ceremony in Pakraman Suwat Village. The research carried out uses several theories to dissect the problems discussed. The theories used are the theory of religion, structural functional theory, and symbol theory. The research method is qualitative research with a philosophical approach. The type of data used is qualitative data in the form of information sourced from informants and literature, quantitative data in the form of numerical figures relating to population data, while the data sources used are primary data obtained from interviews, and secondary data obtained from relevant literature. with a research problem. Determination of informants using purposive sampling technique which is a technique of determining informants based on the ability of the informants who can accurately provide the necessary data in accordance with the objectives of the researcher. Data were collected using observation, interview, and document recording techniques. The data that has been collected is processed using descriptive qualitative methods. The research findings obtained, the form of implementation of the Munggah Deha Ceremony can be seen from the history of the Munggah Deha Ceremony, the Meaning of the Munggah Deha Ceremony, namely the philosophical meaning, symbolic meaning, ethical meaning, educational meaning and solidarity meaning.